High SARS-CoV-2 Exposure in Feline Residents of a Cat Café in Texas, United States, 2021–2022 - Cassandra Durden; Lisa D. Auckland; Wendy Tang; Gabriel L. Hamer; Sarah A. Hamer (Veterinary Sciences)
Congregate animal settings can serve as foci for the increased transmission of pathogens, including zoonoses. Domestic cats have been shown to be reservoirs for SARS-CoV-2 but the public health importance of infected cats has not yet been determined. A population of indoor-only residential cats at a cat café in central Texas with a high level of human interaction was evaluated for infection with SARS-CoV-2 in a longitudinal study in 2021–2022. Among 25 cats, none were qRT-PCR-positive, while 50% harbored SARS-CoV-2-neutralizing antibodies, including 1 that remained seropositive for >8 months. The high level of human exposure in this unique congregate cat setting—in which dozens of new visitors interact with the cats every day—likely facilitated the human-to-cat transmission of SARS-CoV-2 that led to a 50% infection prevalence in cats. This work was conducted when the Delta and Omicron variants predominated. Given that feline susceptibility to infection and shedding of a virus may vary across different viral variants, veterinary surveillance may be an important component of veterinary and human health risk assessments.